Plexiform Neurofibroma of the Wrist: Imaging Features and When to Suspect Malignancy - Maria Gosein; Anthony Ameeral; Renee Banfield; Murrie Mosodeen (Case Reports in Radiology)
Plexiform neurofibromas are essentially pathognomonic for neurofibromatosis type 1 (NF1), occurring when there is diffuse involvement along a nerve segment and its branches. Transformation into a malignant peripheral nerve sheath tumour (MPNST) is a major cause of mortality in NF1 patients. These tumours are highly aggressive and particularly difficult to diagnose in NF1 patients due to the clinical overlap between benign and malignant lesions. We present a case of a plexiform neurofibroma and discuss the typical imaging characteristics on ultrasound, CT, and MRI, including the target sign and continuity with the parent nerve. Certain imaging features should raise suspicion for malignancy however, these modalities may not always reliably differentiate between benign and malignant lesions. Recent studies show a very high negative predictive value for FDG-PET making it quite useful in excluding malignancy. In positive scans, PET/CT aids in guiding biopsy to the most metabolically active area of the tumour.